Excitation-emission fluorescence spectroscopic analysis in the presence of interferents: A laboratory experiment integrating analytical chemistry and advanced data processing - Boeris, Valeria (2013)
In the present report an advanced experiment is described to introduce chemistry students to the direct chemometric resolution of binary mixtures of two pharmaceuticals (oxatomide and phenylephrine) by measuring excitation-emission fluorescence matrices, and processing them with second-order calibration based on a decomposition algorithm called parallel factor analysis (PARAFAC). This experiment is of interest because it combines experimental analytical chemistry (preparation of standard solutions, spectrofluorimetric measurements, etc.) with computer applications not requiring deep programming skills. Second-order multivariate calibration was implemented with a simple graphical toolbox especially designed for this report: mvc2basic, which is available as supplementary material. This work provides students the opportunity to be introduced to advanced chemometrics activities in an accessible manner.